Managing Intergroup Attitudes among Hong Kong Adolescents: Effects of Social Category Inclusiveness and Time Pressure - LAM, Shui Fong (Institutional Knowledge at Singapore Management University, 2006)
Previous research has shown a widespread bias among Hong Kong adolescents against Chinese Mainlanders. Based on social identity and social cognitive theories, we examined the effects of identity frame switching (situational induction of social category inclusiveness) and time pressure (environmental constraints on social information processing) on Hong Kong adolescents’ attitudes toward Chinese Mainlanders. Results indicated that Hong Kong adolescents had acquired a habitual tendency to make social comparisons within an exclusive regional framework of reference. This habitual tendency might lead to negative judgment biases toward Chinese Mainlanders, particularly when the adolescents made social judgments under time pressure. In addition, switching to an inclusive national frame of reference for social comparison attenuated negative intergroup attitudes. The theoretical implications of these findings are discussed.